KLIPPEL-TRENAUNAY SYNDROME: A RARE CAUSE OF INTERMITTENT LOWER GASTROINTESTINAL BLEEDING - Khan, Abbas; Khan, Hashmatullah; Hassan, M. Kamran; Khan, Aamir Ghafoor; Khan, Naimatullah; Saifullah, Zaffar; Nawaz, Ahmad (Journal of Postgraduate Medical Institute, 2012)
Klippel-Trenaunay syndrome is a rare non-hereditary congenital abnormality characterized by a clinical triad of soft tissue hypertrophy of extremity, varicosities and cutaneous hemangiomas or lymphongioma. Bleeding per rectum is an uncommon but potentially serious complication. We herein report a case admitted to the gastroenterology ward Postgraduate Medical Institute, Lady Reading Hospital Peshawar, with intermittent haematocezia and symptomatic iron deficiency anemia .The patient did not seek any help for gastrointestinal bleeding until his admission to our unit. He was also having gigantism of his right leg and port wine angiomatous spots on his buttocks and leg. The literature on the evaluation and management on this case is reviewed.